2019
DOI: 10.1038/s41586-019-0917-9
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-large library docking for discovering new chemotypes

Abstract: Despite intense interest in expanding chemical space, libraries of hundreds-of-millions to billions of diverse molecules have remained inaccessible. Here, we investigate structure-based docking of 170 million make-on-demand compounds from 130 well-characterized reactions. The resulting library is diverse, representing over 10.7 million scaffolds otherwise unavailable. The library was docked against AmpC β-lactamase and the D 4 dopamine receptor. From the top-ranking molecules, 44 and 549… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
1,024
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 788 publications
(1,043 citation statements)
references
References 71 publications
9
1,024
1
9
Order By: Relevance
“…Collectively, our results strongly support the use of docking the largest available compound library for identifying novel potent scaffolds or chemicals, as concluded by Lyu et al. [31]…”
Section: Wwwmolinfcomsupporting
confidence: 89%
See 2 more Smart Citations
“…Collectively, our results strongly support the use of docking the largest available compound library for identifying novel potent scaffolds or chemicals, as concluded by Lyu et al. [31]…”
Section: Wwwmolinfcomsupporting
confidence: 89%
“…Second, ROC AUC value for Glide SP used to dock 81 Mpro inhibitors and~4,000 decoys was 0.72, similarly to the more computationally expensive Glide XP protocol (Figure 1b), and 0.74 when active molecules were diluted in 1 million random compounds extracted from ZINC15 (Figure S1 in supplementary material). Thus, in light of recent studies advocating for extending virtual screening to large chemical libraries when docking works well at smaller scales, [31] we decided to use Glide SP as DD docking program to screen ZINC15 against SARS-CoV-2 Mpro. DD relies on a deep neural network trained with docking scores of small random samples of molecules extracted from a large database to predict the scores of remaining molecules and, therefore, discard low scoring molecules without investing time and resources to dock them.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[241] Recently,t his ultralarge virtuall ibrary was used to discover novel, highly potent AmpC b-lactamase inhibitors and D 4 dopamine receptor ligands. [251]…”
Section: Exploration Of Virtual Chemical Space Guided By Synthetic Acmentioning
confidence: 99%
“…[5] The largest docking study reported to date includes the virtual screening of a total of 170 million make-on-demand compounds against AmpC β-lactamase and the D 4 dopamine receptor, as a result of which several novel and, in part, highly potent inhibitors of these proteins were identified. [6] Despite these successes, the ability of scoring functions to estimate in particular absolute ligand binding affinities remains clearly limited, [7,8] which is related to the inadequate consideration of protein flexibility, [9,10] solvation effects, [10,11] and entropy. [12] The computational costs involved in sampling the relevant conformational states of biomacromolecules are often prohibitive to the consideration of protein flexibility and solvation in docking, in particular in the context of virtual screening.…”
Section: Introductionmentioning
confidence: 99%